Prospects of Microstrip Waveguides in Aluminum and Copper Metallization for High-Frequency Applications 10.14209/jcis.2003.1 - Kehrer, Daniel; Steinlesberger, Gernot; Aufingcr, Klaus; Tischer, Harald; Wohlmuth, Hans-Dieter; Simburger, Verner; L. Scholtz, Arpad (Journal of Communication and Information Systems, 2015)
An electrical characterization of the high-frequency behavior of monolithically integrated microstrip waveguides and a grounded coplanar line is presented. Microstrip lines fabricated with both aluminum metallization and copper metallization are compared in detail. Scaling laws and future metallization technologies are discussed. The waveguides are characterized by S-parameter measurements in a frequency range from 100 MHz to 80 GHz. After deembedding the characteristic impedance, propagation constant and telegraphers equation transmission parameter are extracted. Measurement results are compared to simulation results in detail. Advantages of aluminum and copper metallization are discussed.